NCOR2 is a novel candidate gene for migraine-epilepsy phenotype. (June 2022) - Nuottamo, Marjo Eveliina; Häppölä, Paavo; Artto, Ville; Hautakangas, Heidi; Pirinen, Matti; Hiekkalinna, Tero; Ellonen, Pekka; Lepistö, Maija; Hämäläinen, Eija; Siren, Auli; Lehesjoki, Anna-Elina; et al.
Hypothesis: To identify genetic factors predisposing to migraine-epilepsy phenotype utilizing a multi-generational family with known linkage to chr12q24.2-q24.3. Methods: We used single nucleotide polymorphism (SNP) genotyping and next-generation sequencing technologies to perform linkage, haplotype, and variant analyses in an extended Finnish migraine-epilepsy family (n = 120). In addition, we used a large genome-wide association study (GWAS) dataset of migraine and two biobank studies, UK Biobank and FinnGen, to test whether variants within the susceptibility region associate with migraine or epilepsy related phenotypes in a population setting. Results: The family showed the highest evidence of linkage (LOD 3.42) between rs7966411 and epilepsy. The haplotype shared among 12 out of 13 epilepsy patients in the family covers almost the entire NCOR2 and co-localizes with one of the risk loci of the recent GWAS on migraine. The haplotype harbors nine low-frequency variants with potential regulatory functions. Three of them, in addition to two common variants, show nominal associations with neurological disorders in either UK Biobank or FinnGen. Conclusion: We provide several independent lines of evidence supporting association between migraine-epilepsy phenotype and NCOR2 . Our study suggests that NCOR2 may have a role in both migraine and epilepsy and thus would provide evidence for shared pathophysiology underlying these two diseases.